Distensibility of the anal canal in patients with idiopathic fecal incontinence: a study with the Functional Lumen Imaging Probe. Issue 2 (29th November 2013) - Sørensen, G.; Liao, D.; Lundby, L.; Fynne, L.; Buntzen, S.; Gregersen, H.; Laurberg, S.; Krogh, K.
Abstract Background Anatomical structures and their distensibility vary along the length of the anal canal. The anal sphincter muscles have dynamic properties that are not well‐reflected by standard manometry. Abnormal distensibility of the anal canal may be of importance in idiopathic fecal incontinence (IFI). The functional lumen imaging probe (FLIP) allows detailed studies of the distensibility and axial variation of sphincters. We aimed at comparing segmental distensibility of the anal canal in patients with IFI and healthy subjects. Methods The FLIP was used for distension of the anal canal in 22 patients with IFI (17 female, age 27–82 years) and 21 healthy volunteers (18 female, age 32–73 years). The distensibility was determined from changes in luminal diameter. Closure of the anal canal during voluntary squeeze was computed as the combined length of closed anal canal and time. Pressure‐strain elastic modulus was computed at rest. Key Results In all subjects, the proximal anal canal was the most distensible segment. During distension at rest and during squeeze the middle and distal anal canal became significantly larger in IFI than in healthy (F < 22.4, p < 0.05). The closure of the anal canal during voluntary squeeze did not differ between healthy (75.9 ± 92.9 mm s) and IFI patients (90.4 ± 105 mm s; p = 0.6). Compared with healthy, IFI patients had lower pressure‐strain elastic modulus of the middle and distal (q > 4.5, p < 0.05) but not the proximal anal canal (q < 0.7, p > 0.05). Conclusions & Inferences Patients with IFI have increased distensibility of the middle and distal parts of the anal canal.